2007
DOI: 10.1007/s10546-006-9151-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term comparisons of net radiation calculation schemes

Abstract: Six commonly used models for calculating daily net radiation were tested against measured net radiation. Meteorological data from 32 and 7 consecutive years obtained at two temperate sites were used. The extensive duration of the datasets ensured that all weather conditions and extreme events were captured. A set of statistical procedures was used to evaluate the performance of the models. The mean bias errors ranged from 0.0 W m −2 to 24.8 W m −2 and 0.1-24.7 W m −2 and root mean square error from 11.0 W m −2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…The R n -Q g simulated by MV0 had a relatively poor correlation with the observed R n -Q g , as demonstrated by an example from May-October 2008 (Figure 7a). To improve the R n -Q g estimates, the following radiation algorithm recommended by Food and Agricultural Organization (FAO) of the United Nations (Allen et al, 1998, as cited by Kjaersgaard et al, 2007) is examined. The FAO algorithm calculates R n from R s , surface albedo (α s ), and net longwave radiation (R ln , W m -2 ) by:…”
Section: Evaluation Of Mv0 Radiation Modelmentioning
confidence: 99%
“…The R n -Q g simulated by MV0 had a relatively poor correlation with the observed R n -Q g , as demonstrated by an example from May-October 2008 (Figure 7a). To improve the R n -Q g estimates, the following radiation algorithm recommended by Food and Agricultural Organization (FAO) of the United Nations (Allen et al, 1998, as cited by Kjaersgaard et al, 2007) is examined. The FAO algorithm calculates R n from R s , surface albedo (α s ), and net longwave radiation (R ln , W m -2 ) by:…”
Section: Evaluation Of Mv0 Radiation Modelmentioning
confidence: 99%
“…For linear regression analysis most commonly used equation (Kjaersgaard et al, 2007) to estimate net radiation at the surface is…”
Section: Linear Modelsmentioning
confidence: 99%
“…However, it is extremely difficult to generate a complete set of atmosphere and surface products for model calculation at a high resolution. The most practical solution is to estimate incident shortwave radiation directly from satellite observations and then convert it into all-wave net radiation using either linear [30][31][32][33][34] or nonlinear [35,36] models. Jiang et al [37] recently developed two artificial neuron networks models using comprehensive global in situ observations and found that the nonlinear models can produce better accuracy than the linear models.…”
Section: Introductionmentioning
confidence: 99%